Syndromes and a Century - Weerasethakul, Apichatpong; Mukdeeprom, Sayombhu; Sawaddikul, Nantarat; Iamaram, Jaruchai; Nimsomboon, Nu (bfi, 2008)
"Syndromes and a Century", the fifth feature from Thai director Apichatpong Weerasethakul is a spellbinding Buddhist meditation on the mysteries of love and attraction, the workings of memory, and the ways in which happiness is triggered. Mesmerisingly beautiful to look at, it is also laced with wonderful absurd humour ... Dubbed 'a hospital comedy of a somewhat metaphysical bent', "Syndromes and a Century" is inspired by the Weerasethakul's memories of his parents, both doctors, and of growing up in a hospital environment. The two central characters interact with a bizarre array of professional colleagues and patients with their various strange maladies, including an elderly haematologist who hides her whisky supplies in a prosthetic limb, a Buddhist monk suffering from bad dreams about chickens, and a young monk who once dreamed of being a DJ and now forms an intense bond with a singing dentist whom he believes to be the reincarnation of his dead brother. [bfi.org.uk]